2018
DOI: 10.1039/c7em00533d
|View full text |Cite
|
Sign up to set email alerts
|

Emerging investigator series: methylmercury speciation and dimethylmercury production in sulfidic solutions

Abstract: Alkylated mercury species (monomethylmercury, MeHg, and dimethylmercury, DMeHg) exhibit significant bioaccumulation, and pose significant risks to ecosystems and human health. Although decades of research have been devoted to understanding MeHg formation and degradation, little is known about the DMeHg formation in aquatic systems. Here, we combine complementary experimental and computational approaches to examine MeHg speciation and DMeHg formation in sulfidic aqueous solutions, with an emphasis on the format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 69 publications
0
40
0
Order By: Relevance
“…The relative concentration of sulfide would also influence MeHg speciation, as previous studies have suggested that abiotic MeHg decomposition can occur in sulfidic environments. 49 54 …”
Section: Resultsmentioning
confidence: 99%
“…The relative concentration of sulfide would also influence MeHg speciation, as previous studies have suggested that abiotic MeHg decomposition can occur in sulfidic environments. 49 54 …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, HgS was also formed during the decomposition of (MeHg) 2 S. In nonbiological samples, Craig and Bartlett previously observed biphasic decay of MeHg in the presence of H 2 S in an aqueous reaction mixture, with an initial rapid decay and then a slow decay that were probably due to the formation of (MeHg) 2 S, which is a somewhat water-insoluble material, and evolution of DMeHg from the reaction mixture, respectively 27 , thus supporting the results of our cell-free study. We performed a series of experiments and suggested that H 2 S generated in sediments may accelerate the transformation of MeHg to volatile DMeHg, which moves to the atmosphere 27 29 . To our knowledge, previous reports have not focused on the biotransformation of (MeHg) 2 S to DMeHg in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Of the various Hg species, the Henry's law coefficients of Hg 0 and dimethylmercury (DMHg) indicate they are highly volatile and could volatilize from the dissolved phase at ambient temperatures. Recent studies have shown the potential abiotic pathways of DMHg formation from MeHg mediated by reduced sulfur groups on mineral or organic surfaces (Jonsson et al ), and in sulfidic aqueous solutions (Kanzler et al ). To verify whether DMHg was produced in our experiments as well as distinguish Hg 0 from DMHg in the gas traps, we used another Hg trap, Bond Elut ENV (Agilent Tech., Santa Clara, California), which contains styrene‐divinylbenzene polymeric resins and effectively collects volatile organomercury compounds (Baya et al ).…”
Section: Methodsmentioning
confidence: 99%
“…The Hg 0 production in MeHg-treated cultures at 4 C was similar to that of gross but greater than net production rates in Hg(II)-treated cultures at 4 C. Because gas formation in Hg(II)treated seawater was much more influenced by temperature than in MeHg-treated seawater, it appears that the demethylation process might not be as sensitive to temperature as reduction of Hg(II) or, the gross demethylation process might be partially driven by an uncharacterized abiotic reaction which is not affected appreciably by temperature. Alternatively, abiotic MeHg degradation with thiols (Jonsson et al 2016) and sulfides (Kanzler et al 2018) to form DMHg has been shown to occur spontaneously. No sulfide was added in our treatments, but DMHg formation might be achieved if MeHg reacts with reduced sulfur groups on microbial cell surfaces.…”
Section: Effects Of Temperature and Lightmentioning
confidence: 99%